Palliative care pathways in Amyotrophic Lateral Sclerosis (ALS): a sequence analysis of health claims data - Richard Schmidt; Ekaterina Slotina; Franziska Meissner; Moritz Metelmann; Benjamin Ilse; Verena Vogt; Antje Freytag (BMC Palliative Care)
Abstract Background Amyotrophic lateral sclerosis is a progressive neurodegenerative disease requiring palliative care. Despite the availability of palliative care services, utilization patterns among people with ALS (pALS) remain poorly understood. This study aimed to analyze palliative care utilization (i.e., primary palliative care (PPC), specialized palliative homecare (SPHC), inpatient palliative care, hospice services) in the last year of life among pALS, to identify distinct care pathways using sequence analysis, and examine their association with end-of-life care quality. Methods A retrospective cross-sectional study using German health claims data (2016 – 2019). Sequence analysis with Temporal Needleman-Wunsch alignment and clustering identified pathway clusters based on type, order, and timing of palliative care services. The study included 1,295 pALS who died between 2016 and 2019 and were insured with a large German health insurance provider. Inclusion required an ALS diagnosis without concurrent cancer. Results Of 1,295 pALS, 695 (53.7%) received palliative care. Sequence analysis identified nine distinct care pathway clusters. Quality indicators varied highly across clusters. Pathways involving SPHC, either alone, with PPC, and/or with hospice care, showed fewer emergency visits, hospital stays, and in-hospital deaths, suggesting higher end-of-life care quality. Conclusions Palliative care utilization varies substantially in type, order, and timing. Findings suggest that end-of-life care quality depends not only on the provision of palliative care but also on when and on how different services are combined. Future research should examine the role of interdisciplinary collaboration in palliative care pathways and explore preferences and clinical characteristics of pALS to better understand factors influencing end-of-life care quality.